Googling inclusive education: a critical visual analysis. Issue 2 (4th March 2022) - Walton, Elizabeth; Dixon, Kerryn
ABSTRACT: Inclusive education is a global rights-based response to educational exclusion. It is communicated through a range of modalities, but analysis predominantly focuses on discourses constituted in written texts. Systematic research is needed to understand the discursive ensembles constituted by the visual mode. Our interest is in images of inclusive education that are available online and sourced via a Google images search. Using a critical approach to visual analysis, we conducted a visual content analysis and a multimodal discourse analysis. Four prominent discourses of inclusive education are evident: discourses of diversity, childhood, connection, and celebration. Education is a discursive absence. Each discourse reflects ideas of the field, but together these images present a distorted view of inclusive education and trivialise its concerns. This raises questions about the extent to which images can adequately capture the complexity and import of notions of access, equity and social justice.